1991
DOI: 10.1177/030098589102800509
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Venezuelan Equine Encephalitis Virus Infection in Mice and Hamsters

Abstract: Abstract. Th e pathogenesis of Venezuelan eq uine encephalitis (VEE) viru s infection was compared in intraperitoneally inoc ulated mice (n = 24, 6 to 8 weeks old) and ham sters (n = 9, 90-110 g) using histopathology and immunohistochemi cal localizati on ofVEE virus antigen. Infected mice developed paralysis, and the majority died by 9 da ys after inoculat ion . In contrast, ham sters did not survi ve beyond 3 days after inoculati on , and they did not develop any neu rologic signs. VEE virus antigen, dem ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 23 publications
3
61
1
1
Order By: Relevance
“…TLR 2, 3, 4 and 7 participate in neuroinflammatory reactions resulting in the increased severity of disease, and are also implicated in inducing apoptosis in epithelial and microglial cells (Yoon et al, 2008;Babcock et al, 2006;Kurt-Jones et al, 2004;Park et al, 2006;Wang et al, 2004;Walter et al, 2007;Caso et al, 2007;Chakravarty & Herkenham 2005;Butchi et al, 2008;Aravalli et al, 2007;Srivastava et al, 2005;Kaiser & Offermann 2005;Haase et al, 2003). Inflammation following VEEV infection is important in conferring protection against VEEV, but neurodegeneration following VEEV infection in the brain is also widely believed to be due to excessive inflammatory response to virus presence in the brain (Charles et al, 2001;Grieder & Vogel, 1999;Jackson et al, 1991;Schoneboom et al, 1999Schoneboom et al, , 2000aWhite et al, 2001). In an earlier study by our laboratory, although direct upregulation of TLRs was not observed, several proinflammatory cytokines, chemokines and apoptotic genes that may also be induced in TLR signalling were upregulated (Sharma et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR 2, 3, 4 and 7 participate in neuroinflammatory reactions resulting in the increased severity of disease, and are also implicated in inducing apoptosis in epithelial and microglial cells (Yoon et al, 2008;Babcock et al, 2006;Kurt-Jones et al, 2004;Park et al, 2006;Wang et al, 2004;Walter et al, 2007;Caso et al, 2007;Chakravarty & Herkenham 2005;Butchi et al, 2008;Aravalli et al, 2007;Srivastava et al, 2005;Kaiser & Offermann 2005;Haase et al, 2003). Inflammation following VEEV infection is important in conferring protection against VEEV, but neurodegeneration following VEEV infection in the brain is also widely believed to be due to excessive inflammatory response to virus presence in the brain (Charles et al, 2001;Grieder & Vogel, 1999;Jackson et al, 1991;Schoneboom et al, 1999Schoneboom et al, , 2000aWhite et al, 2001). In an earlier study by our laboratory, although direct upregulation of TLRs was not observed, several proinflammatory cytokines, chemokines and apoptotic genes that may also be induced in TLR signalling were upregulated (Sharma et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…VEEV enters the CNS primarily through the olfactory tract (Charles et al, 2001;Ryzhikov et al, 1995) and causes encephalitis characterized by neuronal cell death, severe mononuclear cell cuffing of cerebral vessels, meningitis and demyelinating lesions. It is hypothesized that VEEV-induced reactive gliosis and inflammation also leads to the observed secondary neuronal damage in the brain independent of direct virus infection of neuronal cells (Charles et al, , 2001Davis et al, 1994;Grieder et al, 1995;Jackson et al, 1991;Jackson & Rossiter, 1997;Schoneboom et al, 1999Schoneboom et al, , 2000a. Mechanisms underlying the inflammatory response to VEEV infection in the brain are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological sequelae in humans are also common (28). The predominant pathological findings in fatal human VEE cases include infections in (i) the central nervous system (CNS) (edema, congestion, hemorrhages, vasculitis, meningitis, and encephalitis), (ii) the lungs (interstitial pneumonia, alveolar hemorrhage, congestion, and edema), (iii) lymphoid tissue (follicular necrosis and lymphocyte depletion), and (iv) the liver (diffuse hepatocellular degeneration) (9,10,22).A murine model for VEEV-induced encephalitis and lymphotropism is well established (7,8,18,27). Subcutaneous infection of mice leads to biphasic disease with initial replication in lymphoid tissues, followed by viremia and penetration into and infection of the central nervous system (40), where the virus replicates until death of the infected animal occurs (12,13,16,39).…”
mentioning
confidence: 99%
“…Lesions appear that are surrounded by necrotic cellular debris, perivascular cuffs composed of mononuclear cells, rarefaction of the neuropil and infiltration of neutrophils lymphocytes and macrophages. These lesions spread following the virus by an approximately 24 h delay from olfactory bulb to more caudal regions (Jackson, et al, 1991;Jensen & Jackson, 1966;Ludwig, et al, 2001;Ryzhikov, et al, 1991;Steele, et al, 1998;Steele, et al, 2006;Stephenson, et al, 1988;Vogel, et al, 1996). Once in the CNS viral tropism is primarily neuronal though CNS macrophages as well as astrocytes may become infected with VEEV, but do not appear to be a primary target (Jackson & Rossiter, 1997a;Schoneboom, et al, 2000b;Steele, et al, 1998;Steele, et al, 2006).…”
Section: Mouse Modelmentioning
confidence: 99%
“…In guinea pigs and hamsters, VEEV causes acute, fulminant disease associated with extensive necrosis of lymphoid tissues, and death typically occurs prior to development of CNS disease making these models limited for studies of human infections and encephalitis (Gorelkin & Jahrling, 1975;Jackson, et al, 1991;Jahrling & Scherer, 1973a;Jahrling & Scherer, 1973b;1973c;Walker, et al, 1976) …”
Section: Hamster and Guinea Pig Modelsmentioning
confidence: 99%